Syntheses, characterizations of copper compounds containing a series of S-, N-containing aromatic heterocyclic 2, 2′:6′, 2″-terpyridine derivatives. Issue 24 (16th December 2016) - Wang, Na; Chang, Fei-Fan; Peng, Yu-Xin; Qian, Hui-Fen; Huang, Wei
Abstract: A series of 2, 2′:6′, 2″-terpyridine (TPY) based aromatic heterocyclic compounds, extended by thiophene, 4-dibenzothiophene, and thiazole units at the para position of the central pyridine ring in TPY, are described in this paper. A new compound, 4′-(4′-dibenbenzothiophene-5-thiophene-2-yl)-2, 2′:6′, 2″-terpyridine (La ), serves as a tridentate ligand to react with Cu(NO3 )2 ·3H2 O and CuCl2 ·2H2 O, respectively, to produce two different Cu(II) complexes [Cu(La )2 ](NO3 )2 and [CuLa Cl2 ] with 1 : 2 and 1 : 1 metal/ligand ratios. Dibenzothiophene is first introduced to TPY via the thiophene bridge. The alterations in cis and trans configuration, dihedral angles between adjacent aromatic rings, and photophysical properties have been observed before and after Cu(II) complexation, which has been verified by their crystal structures, UV–vis and fluorescence spectra. Abstract :